2020
DOI: 10.3389/fnins.2020.575771
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Response to Group Cognitive Behavioral Therapy in Asthma by a Small Number of Abnormal Resting-State Functional Connections

Abstract: Group cognitive behavioral therapy (GCBT) is a successful psychotherapy for asthma. However, response varies considerably among individuals, and identifying biomarkers of GCBT has been challenging. Thus, the aim of this study was to predict an individual’s potential response by using machine learning algorithms and functional connectivity (FC) and to improve the personalized treatment of GCBT. We use the lasso method to make the feature selection in the functional connections between brain regions, and we util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…As comorbid asthma-panic disorder (PD) occurs at a high rate in the population, it was reported that cognitive behavior psychophysiological therapy (CBPT) and music and relaxation therapy (MRT) both showed advantages in obviously reducing respiration rate, blood pressure, heart rate, and anxiety to help improve asthma control, in which CBPT was superior to MRT in improving the adherence to ICS [ 50 ]. Furthermore, group cognitive behavioral therapy (GCBT) might modulate the autonomic nervous system and supplementary motor area (SMA) to adjust breathing, encourage asthmatic patients to overcome their worry and panic, and recover abnormal functional connectivity (FC) for better symptom control [ 51 ].…”
Section: Advances In Research On Asthmamentioning
confidence: 99%
“…As comorbid asthma-panic disorder (PD) occurs at a high rate in the population, it was reported that cognitive behavior psychophysiological therapy (CBPT) and music and relaxation therapy (MRT) both showed advantages in obviously reducing respiration rate, blood pressure, heart rate, and anxiety to help improve asthma control, in which CBPT was superior to MRT in improving the adherence to ICS [ 50 ]. Furthermore, group cognitive behavioral therapy (GCBT) might modulate the autonomic nervous system and supplementary motor area (SMA) to adjust breathing, encourage asthmatic patients to overcome their worry and panic, and recover abnormal functional connectivity (FC) for better symptom control [ 51 ].…”
Section: Advances In Research On Asthmamentioning
confidence: 99%